A phase I dose-escalation study of neoantigen-activated haploidentical T cell therapy for the treatment of relapsed or refractory peripheral T-cell lymphoma - Chen, Yuan; Zhao, Hu; Luo, Jing; Liao, Youping; Dan, Xu; Hu, Guoyu; Gu, Weiyue (Frontiers in Oncology, 2022)
Peripheral T-cell lymphoma (PTCL) is a type of highly heterogeneous non-Hodgkin lymphoma with a poor prognosis and lack of effective targeted therapies. Adoptive T-cell therapy has been successfully used in the treatment of B-cell malignancies. We first used adoptive transfer of haploidentical T cells activated by patient-specific neoantigens in vitro to treat an elderly patient with refractory angioimmunoblastic T-cell lymphoma (AITL) in 2017, and the patient achieved long-term complete remission (CR). Here we report on early results from this first-in-human phase 1 clinical trial that aims to assess the safety and tolerability of neoantigen-activated haploidentical T cell therapy (NAHTC) for relapsed/refractory PTCL. Clinical trial registration http://www.chictr.org.cn/index.aspx, identifier [ChiCTR1800017440].